A packaged mindset: How elongated packages induce healthy mindsets. (1st July 2020) - Sheehan, Daniel; Van Ittersum, Koert; Craig, Adam w.; Romero, Marisabel
Abstract: Product packaging is an important instrument for marketers to draw consumer attention to specific product information and influence product perceptions. The purpose of this research is to investigate whether exposure to a product's packaging can also activate specific mindsets that, once activated, alter consumers' food perceptions. The results of three experiments demonstrate that elongated containers activate a health mindset that influences both consumers' perception of the packaged food product but also their health perceptions of subsequently encountered food. Specifically, foods in elongated containers lead consumers to think of concepts related to healthiness, which have differentiable effects on subsequent healthy and unhealthy food products.